THE MEANING OF THE LITERARY TEXT – READER’S INDIVIDUAL ACT - Buba Stojanović (Facta Universitatis. Series, Teaching, Learning and Teacher Education, 2021)
The relationship between a literary text and a reader, and especially the triad the author – the text – the reader are complex phenomena that have been studied from different perspectives in the science of literature. However, the least attention has been paid to the reader as an important, if not the most important factor in the process of successfully revealing numerous potential meanings of the literary text. Only at the beginning of the 20th century did the reader become a significant component in the interpretation of the text. Many scientific disciplines have become interested in the reader, while his emotional sensitivity, motivation to read, depth of experience and level of mental engagement have become crucial for all possible meanings of the text. The reader becomes the key element in the process of understanding the text, whose dedication and level of reception and the future fate of the text will depend on. Starting from Ingarden’s claim that there are two different phases of interpreting a literary text (while-reading and post-reading phase), and having in mind the need to educate a true, dedicated, realistic reader, this paper highlights the importance of good motivation for experiencing and understanding a text as a prerequisite for nurturing a literary taste, developing the emotional sensitivity and individuality of a person from an early age. Understanding a literary text, whether by listening or reading, implies a mentally active recipient who is fully engaged in both phases and in direct contact with the text, and he discovers, interprets and re-creates the literary text based on his personal experience, while at the same time advancing himself spiritually, aesthetically and emotionally with new meanings that the text radiates. That is why the approach to a literary text should always be open-minded and new, it should look for unexpected, original answers that are an expression of the reader’s individual experience.